Neemias: o ethos do homem que reconstruiu Jerusalém - Palma, Wagno Broedel (2020)
The process of rising and downfall of societies is something common throughout human history. Consequently, several civilizations have suffered such a phenomenon and eventually faced their ruin. The Jerusalem destruction in 586 BC, by the Babylonian king Nebuchadnezzar II, is a great example of that phenomenon. The temple was burned down, the city was completely shattered, and the great wall which surrounded the city was smashed. The noble people, as well as the governors and craftsmen, were enslaved. Many died trying to fight against such a tragedy and a few people were left to sink or swim – mostly poor widows, orphans, and workers. In 538 BC the Persians defeated the Babylonian, and Cyrus II allowed the exiled people to return to their homes and rebuild them. In the same year, the Jewish returned to Jerusalem and started to rebuild their temple. However, problems with their rivals prevented the reconstruction for more than 70 years. The city and citizens luck changes with Nehemiah, in 545 BC. His discourses and actions are stated in the biblical book named after him. In this study, the twelve pericopes – from the first five chapters in the book of Nehemiah, are selected as an analytical subject. Those pericopes will be analyzed from a rhetorical perspective. The definitions of Rhetoric, provided by several authors, will base the starting point of the study. Then, the discourses from the analytical subject will be described according to their rhetorical genre. Concluding, the ethos concept will be analyzed in several instances of the discourses to unveil their rhetorical strength and persuasive matter according to their audiences. The bibliographical method leads this study development in the following steps: First, the rhetorical part of the study will be carried, considering authors such as Aristotle (2005), Cicero (1997; 2002), The author of Rhetorica ad Herennium (1997), Quintilian (2004), Augustine of Hippo (2002), Perelman and Olbrechts-Tyteca (2017), Reboul (2004), Meyer (2007), and Figueiredo and Ferreira (2016). Second, the description and interpretation of the study object will take place, according to the biblists Abadie (1998), Ceresko (2011), Díaz (2015), Gass (2017), Lamadrid (2015), Lopes (2006), Mackenzie (1984), Sacardelai (2012), Tünnermann (2001), and Villac (2007). After these two steps, a qualitative analysis will be carried out. Thus, the Nehemiah book, chapters one to five, will be analyzed rhetorically. The relevance of this study lies in such a historical event, as well as the importance of Nehemiah’s persuasive discourses to history, and the scientific gap created by this biblical figure. Finally, it is expected to unveil Nehemiah as a great orator. An orator that achieved his persuasive goal – the reconstruction of Jerusalem, by the power of his ethos. Keywords: Rhetoric, Ethos; Bible; Jerusalem; Nehemiah.